INTERPOLATIONS OF SPATIAL DATA ON THE BASIS OF SURFACES FOR THE PROGRAMMATIC TOOLS OF THE GEOINFORMATICAL SYSTEMS (GIS) - Ріпецький, Роман Йосипович; Сеничак, Василь Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Formulated task to describe mathematically the character of distributing of spatial sign on territory from data of point supervisions. The decision of task is related to development of methods of interpolation. TIN-surfaces and grid-surfaces are used. On the basis of the interstratified analysis the equalization is got for linear interpolation of spatial data in programmatic tools GIS. The got methods are tested for construction of map of contamination of territory.